The relationship between exposure to violent scenes during collecting and preparing of news and Anxiety among a sample of communiceters in Damascus state. - ALkenane, Ahmad (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The present research aimed at revealing the nature of the relationship between exposure to violent scenes during collecting and preparing of news to Anxiety among a sample of communiceters in Damascus state. The research attempted to determine the degree of exposure to violent scenes, and to disclose the nature of the differences between males and females in each of exposure to violent scenes and Anxiety. The sample of the research consisted of (103) communiceters, the number of male communiceters was (84) and, the number of female communiceters was (19). The tools of the research included a questionnaire of exposure to violent scenes and a test of state- trait Anxiety STAI, and were verified to ensure their validity and reliability by using appropriate scientific methods. This research came up with the following results: - There is a negative statistical significant relationship at the level of significance 0.01 between tests of exposure to violent scenes and Anxiety. -There are statistical significant differences at the level of significance 0.05 between males and females in exposure to violent scene. -There are no statistical significant differences at the level of significance 0.05 between males and females in Anxiety.